Codonopsis lanceolata Contributes to Ca2+ Homeostasis by Mediating SOCE and PLC/IP3 Pathways in Vascular Endothelial and Smooth Muscle Cells - Kim, Min Kyung; Han, A Young; Shin, You Kyoung; Lee, Kwang-Won; Seol, Geun Hee (Planta Medica, 2020)
Codonopsis lanceolata has been widely used as an anti-inflammatory and anti-lipogenic agent in traditional medicine. Recently, C. lanceolata was reported to prevent hypertension by improving vascular function. This study evaluated the effects of C. lanceolata and its major component lancemaside A on cytosolic calcium concentration in vascular endothelial cells and vascular smooth muscle cells. Cytosolic calcium concentration was measured using fura-2 AM fluorescence. C. lanceolata or lancemaside A increased the cytosolic calcium concentration by releasing Ca2+ from the endoplasmic reticulum and sarcoplasmic reticulum and by Ca2+ entry into endothelial cells and vascular smooth muscle cells from extracellular sources. The C. lanceolata- and lancemaside A-induced cytosolic calcium concentration increases were significantly inhibited by lanthanum, an inhibitor of non-selective cation channels, in both endothelial cells and vascular smooth muscle cells. Moreover, C. lanceolata and lancemaside A significantly inhibited store-operated Ca2+ entry under pathological extracellular Ca2+ levels. In Ca2+-free extracellular fluid, increases in the cytosolic calcium concentration induced by C. lanceolata or lancemaside A were significantly inhibited by U73122, an inhibitor of phospholipase C, and 2-APB, an inositol 1,4,5-trisphosphate receptor antagonist. In addition, dantrolene treatment, which inhibits Ca2+ release through ryanodine receptor channels, also inhibited C. lanceolata- or lancemaside A-induced increases in the cytosolic calcium concentration through the phospholipase C/inositol 1,4,5-trisphosphate pathway. These results suggest that C. lanceolata and lancemaside A increase the cytosolic calcium concentration through the non-selective cation channels and phospholipase C/inositol 1,4,5-trisphosphate pathways under physiological conditions and inhibit store-operated Ca2+ entry under pathological conditions in endothelial cells and vascular smooth muscle cells. C. lanceolata or lancemaside A can protect endothelial cells and vascular smooth muscle cells by maintaining cytosolic calcium concentration homeostasis, suggesting possible applications for these materials in diets for preventing vascular damage.
Keywords: Codonopsis lanceolate; Campanulaceae; store-operated Ca2+ entry; inositol 1,4,5-trisphosphate; vascular endothelial cells; vascular smooth muscle cells